Perancangan Interior Galeri Patung Lilin Tokoh Srimulat di Surabaya dengan Konsep "A Comedian Journey As Friend" - Poppy F.Nilasari, Eric Hariyanto Martino Dwi Nugroho (Intra, 2014)
Srimulat is one artist that is very popular comedy group from Surabaya and people enjoy doing in the 1980s. Wax sculpture is a sculpture made of wax in the melt up to 74 degrees Celsius and a means of supporting the display. For it is necessary to have a tool that can provide a facility to introduce Srimulat with a wax sculpture gallery. In this thesis, the author discusses about the design of a wax sculpture gallery that presents an atmosphere Srimulat periodically and information - information about Srimulat. Taking the concept of "Journey As A Comedian Friend" which is a concept Srimulat journey from the beginning, and to the glorious era terakhinya Srimulat, starting from the creation of space in order to attract visitors by optimizing modern design combined with a pop art style. Srimulat wax figure sculpture gallery is expected to be one - the only place that provides a means of education and introduce Srimulat again to be remembered by the people of Surabaya and Indonesia.